2017
DOI: 10.1088/1748-9326/aa7a1d
|View full text |Cite
|
Sign up to set email alerts
|

Warming in the Nordic Seas, North Atlantic storms and thinning Arctic sea ice

Abstract: Arctic sea ice over the last few decades has experienced a significant decline in coverage both in summer and winter. The currently warming Atlantic Water layer has a pronounced impact on sea ice in the Nordic Seas (including the Barents Sea). More open water combined with the prevailing atmospheric pattern of airflow from the southeast, and persistent North Atlantic storms such as the recent extremely strong Storm Frank in December 2015, lead to increased energy transport to the high Arctic. Each of these sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 86 publications
2
43
0
Order By: Relevance
“…Recent studies have found evidence of an increasing trend in poleward moisture transport toward the GrIS (Mattingly et al, —hereafter M16) and the Arctic basin (Alexeev et al, ; Boisvert & Stroeve, ; Cao et al, ; Gong et al, ; Lee et al, ; Park et al, ; Woods & Caballero, ), in accordance with predictions of enhanced moisture transport to the Arctic in a warming climate (Gimeno et al, ; Graversen & Burtu, ; Lavers et al, ; Yoshimori et al, ). In light of these observed and projected trends, and recent case studies suggesting that ARs may play a significant role in determining the evolution of GrIS SMB, an examination of AR trends and impacts on GrIS SMB across a much larger sample of moisture transport events is needed.…”
Section: Introductionsupporting
confidence: 54%
“…Recent studies have found evidence of an increasing trend in poleward moisture transport toward the GrIS (Mattingly et al, —hereafter M16) and the Arctic basin (Alexeev et al, ; Boisvert & Stroeve, ; Cao et al, ; Gong et al, ; Lee et al, ; Park et al, ; Woods & Caballero, ), in accordance with predictions of enhanced moisture transport to the Arctic in a warming climate (Gimeno et al, ; Graversen & Burtu, ; Lavers et al, ; Yoshimori et al, ). In light of these observed and projected trends, and recent case studies suggesting that ARs may play a significant role in determining the evolution of GrIS SMB, an examination of AR trends and impacts on GrIS SMB across a much larger sample of moisture transport events is needed.…”
Section: Introductionsupporting
confidence: 54%
“…Understanding atmospheric rivers in the Arctic is critical for understanding the local hydrologic regimes, especially as they continue to change due to enhanced warming. There have been few other studies examining the impact of atmospheric rivers in the Arctic (e.g., Alexeev et al, ; Komatsu et al, ; Liu & Barnes, ; Neff et al, ). Similarly, there have been very few studies examining the impact of ARs in Antarctica (e.g., Gorodetskaya et al, ), despite them being critical to local precipitation regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing wildness of weather is becoming a symbol of the Arctic warming. More Atlantic storms penetrate into even higher northern latitudes bringing convective instability and moisture (Alexeev et al, , ; Walsh et al, ; Hao et al, ). Enhanced frequency of the convective cloud types in the WEA and to some degree in the CEA are found in our study for the long period.…”
Section: Discussionmentioning
confidence: 99%